Gymnastics of the Mind : Greek Education in Hellenistic and Roman Egypt - Cribiore, Raffaella (Book collections on Project MUSE., 2005)
This book is at once a thorough study of the educational system for the Greeks of Hellenistic and Roman Egypt, and a window to the vast panorama of educational practices in the Greco-Roman world. It describes how people learned, taught, and practiced literate skills, how schools functioned, and what the curriculum comprised. Raffaella Cribiore draws on over 400 papyri, ostraca (sherds of pottery or slices of limestone), and tablets that feature everything from exercises involving letters of the alphabet through rhetorical compositions that represented the work of advanced students.